Agroforestry System in Saharanpur and Aligarh Districts of Uttar Pradesh: A Socio-economic Analysis - R. P. Dwivedi , K. Kareemulla; R. H. Rizvi (Indian Journal of Extension Education, 2013)
The present study is the outcome of economic diagnosis of traditional as well as commercial agroforestry practices followed by farmers in Western Uttar Pradesh. The field/ farm boundary system of agroforestry has been widely practiced in traditional as well as commercial agroforestry regions. Study revealed that tree species like Azadirachta indica, Acacia nilotica, Dalbergia sissoo and Eucalyptus spp. were dominant species in traditional system whereas, Populus deltoides and Eucalyptus spp. were the main species of commercial agroforestry. Fuel wood (50.6%) was major driving force for agroforestry adoption followed by additional income (24.4%) and shade (17.5%) in traditional agroforestry region while, -1 additional income (71.3%) was the major factor in commercial agroforestry region. The net return from tree produce ha per annum in traditional system was ` 989, 541 and 440 for marginal, small and medium farmers, respectively. In commercial region, B:C ratio has been found higher (3.00) for poplar based agrisilviculture than poplar (2.84) and eucalyptus (2.68) based bund system. Although traditional agroforestry seems less promising as compared to commercial agroforestry, but it is also relevant to the farmers’ livelihood.